Association analysis of fruit traits in mulberry species (Morus L.). Issue 6 (1st November 2016) - Zhang, Jian; Yang, Tongyi; Li, Rong-Fang; Zhou, Yu; Pang, Yun-Long; Liu, Li; Fang, Rong-Jun; Zhao, Qiao-Ling; Li, Long; Zhao, Wei-Guo
ABSTRACT: Improvement of fruit traits is an important objective in current mulberry breeding programs. In this study, 93 mulberry accessions of diverse origin were genotyped using 15 ISSR markers to identify marker–trait associations with fruit traits. Fifteen ISSR primers generated a total of 104 amplification products, of which 94 were polymorphic, revealing 90.38% polymorphism; the mean PIC value was 0.2698. UPGMA cluster analysis showed clear genetic relationships between the 93 mulberry cultivars, and the major clusters were related to known pedigree relationships and their ecotype. The mean r 2 value for all intra-chromosomal loci pairs was 0.0210. Marker–trait associations were investigated using the unified mixed-model approach, considering both population structure (Q) and kinship (K). In total, 24 marker–trait associations ( p < 0.01) were identified using different ISSR markers. The results suggest that association mapping in mulberry is a viable alternative to quantitative trait loci mapping, and detection of associations between markers and mulberry fruit traits will also provide important information for marker-assisted breeding.